2007
DOI: 10.1007/s10802-007-9168-6
|View full text |Cite
|
Sign up to set email alerts
|

Violent Victimization in the Community and Children’s Subsequent Peer Rejection: The Mediating Role of Emotion Dysregulation

Abstract: This paper describes a short-term longitudinal study of the relation between violent victimization in the community and peer rejection among 199 children (mean age = 9.02 years) attending two urban Los Angeles area elementary schools. We used a multi-informant approach to assess victimization by community violence, peer group victimization, peer rejection, and impairments in emotion regulation. These data were collected annually for two consecutive school years. Violent victimization in the community predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 78 publications
2
37
0
2
Order By: Relevance
“…Studies by Schwartz and Proctor (2000) and Kelly et al (2008) found that emotion regulation/stress management mediated violent victimization and social difficulties (i.e., peer rejection, aggression, being a victim of bullying), yet both studies only investigated mediation in the context of direct victimization and externalizing behaviors. The current study's entire sample witnessed some form of violence, thus the sample was not separated based on type of exposure and it is, therefore, unclear whether there would have been differences in current results based on type of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Schwartz and Proctor (2000) and Kelly et al (2008) found that emotion regulation/stress management mediated violent victimization and social difficulties (i.e., peer rejection, aggression, being a victim of bullying), yet both studies only investigated mediation in the context of direct victimization and externalizing behaviors. The current study's entire sample witnessed some form of violence, thus the sample was not separated based on type of exposure and it is, therefore, unclear whether there would have been differences in current results based on type of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The present results also suggest that multiple forms of victimization may be the norm for victimized children, 74 ie, children with a high/chronic trajectory had harsh, reactive parents and were victimized by peers in preschool and after school entry. Other forms of victimization are likely to occur for these children, both within the school (eg, verbal bullying by teachers 75 ) and within the community, 76 particularly within low socioeconomic contexts. 64,65,74 These results suggest that early preventive interventions should target both child-and parent-level risks and focus on alternatives to harsh and aggressive interactions.…”
Section: Commentmentioning
confidence: 99%
“…It may be that children who have poor relationships with peers early in middle school may be at risk for witnessing violence because they do not have the social support that may protect them from exposure or they may be seeking out dangerous situations (Kelly et al, 2008). Further research should attempt to clarify these transactional and reciprocal relationships, as well as try to understand what other variables may be explaining their interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, they may be more likely to place themselves in contexts that are risky and associated with violence exposure (Gorman-Smith and Tolan, 1998). An example of this is seen in children who are victims of violence and as a result begin to act violent towards others, leading them to be more likely to be exposed to violent contexts (Kelly et al, 2008; Halliday-Boykins and Graham, 2001). …”
Section: Exposure To Violence and Social Adjustmentmentioning
confidence: 99%